158k views
4 votes
How can help me with this operation about Pre-Calculus.
Simplify

How can help me with this operation about Pre-Calculus. Simplify-example-1
User Efthymis
by
6.5k points

1 Answer

1 vote

If we want to compute
f(2+h), we have to substitute every occurrence of
x with
2+h in the definition of the function:


f(x)=x^2-11x \implies f(2+h) = (2+h)^2-11(2+h) = 4+4h+h^2-22-11h = h^2-7h-18

Similarly, computing
f(2) means to substitute the input with 2:


f(x)=x^2-11x \implies f(2) = 2^2-11\cdot 2 = 4-22 = -18

So, we have


f(2+h) - f(2) = h^2-7h-18 - (-18) = h^2-7h

And finally


(f(2+h)-f(2))/(h) = (h^2-7h)/(h) = h-7

User Brent Sandstrom
by
5.4k points